Diskrimineringsansvar : En civilrättslig undersökning av förutsättningarna för ansvar och ersättning vid diskriminering - Hellborg, Sabina (Iustus förlag, 2018)
This doctoral thesis examines liability for discrimination under Swedish private law. According to chapter 5, section 1 of the Swedish Discrimination Act (diskrimineringslagen) compensation shall be paid by natural or legal persons who violate the prohibitions of discrimination that are established in the act. The purpose of the compensation is not only to compensate the person discriminated against for the violation of the right to equal treatment, but also to prevent further discrimination. The thesis examines two main questions: (i) what preconditions need to be fulfilled in order to establish liability for discrimination? and (ii) what circumstances affect the amount of compensation? An overarching aim of the thesis is to create an understanding of the characteristic problems and questions that occur when handling discrimination-related questions in a private law context. Consideration is taken to the EU law background and the aim, articulated in EU directives, to achieve effective, proportionate and dissuasive remedies for breaches of the principle of equal treatment. The research focuses on the prohibitions applicable in the working life and regarding goods, services and housing. It includes detailed analyses of the prohibitions against direct discrimination, indirect discrimination, inadequate accessibility, harassment and sexual harassment. The analyses deal with questions concerning the subjective motives of the discriminating party, problematic aspects considering the burden of proof as well as the exceptions from the prohibitions. Circumstances affecting the amount of compensation are analysed considering the character of the discriminating behaviour and its effects. Certain aspects attributable to the preventive function of the damages are examined, as well as how they have been decisive in the court judgements.
Skrifter från Juridiska fakulteten i Uppsala, ISSN 0282-2040 ; 136 URN: urn:nbn:se:uu:diva-347577 OAI: oai:DiVA.org:uu-347577 DiVA, id: diva2:1195232
Keywords: Ansvarsrätt; Diskriminering; Diskrimineringsersättning; Kränkning; Skadestånd; Skadeståndsrätt; Trakasserier